Energy Absorption Performance of Hybrid Bamboo Fibre/Aluminium Mesh Reinforced Polymer Composites Subjected to Axial Crushing Loads - Nik Ismail, Nik Ainun; Roslan, Mohd Nazrul; Ismail, Al Emran; Uyup, Mohd Khairun Anwar (International Journal of Integrated Engineering, 2024)
This study examines the energy absorption capabilities of polymer composites reinforced using a hybrid combination of bamboo fibre and aluminium mesh. The fabrication of the composites involves the utilisation of epoxy resin as a matrix material, which is reinforced with bamboo fibre and an aluminium expanded mesh sheet. This is achieved using the vacuum infusion method, where different stacking sequences and mesh sizes are employed. Two distinct types of tests were conducted in this study: a quasi-static axial crushing test and a dynamic impact test. A comprehensive examination has been conducted to investigate the failure mechanism of the specimens during both testing phases. The energy absorption performance of the specimens has subsequently been evaluated. The findings indicate that specimen A3L exhibited the maximum energy absorption and specific energy absorption compared to all other specimens in both tests. Conversely, specimen A1S demonstrated the lowest energy absorption performance during the test. When comparing the lowest and highest values, this study found that the Energy Absorption (EA) and Specific Eenergy Absorption (SEA) values increased by up to 230% and 125% during the quasi-static test and by 273% and 148% during the dynamic test. An analysis of variance (ANOVA) was conducted on the collected data from both tests in order to determine the elements that significantly impact the energy absorption performance of these composites.